Analisis Konsistensi Implementasi Penggunaan Website pada Proses Rekrutmen dan Seleksi Karyawan Base on Seven Tools Aporoach Method (Studi Kasus PT. Duta Nichirindo Pratama) - Ade Sumaedi (Program Studi Teknik Informatika Universitas Pamulang, 2022)
PT. Duta Nichirindo Pratama is an organization engaged in Autoparts Manufacturing, in this research it focuses on analyzing problems in the personnel department, especially the recruitment and selection process for employees. The previous year the recruitment and selection process for employees was still doing manual queuing and the accumulation of job application letter documents that had the potential to generate waste, from this problem the personnel department immediately made improvements by designing a digital computing website using VB.NET, My.SQL server management and PHP programming language, designed to be a Website Link, namely https://dnp.co.id/employeeactivity. Judging from the problems and improvements that have been made, the title determined in this study is